OPTIMASI KONSENTRASI L-Cysteine PADA MODIFIKASI SINTESIS NANOPARTIKEL PERAK (AgNPs) DENGAN L-Cysteine - Khasanah, Cindi Fitria Nisaul; Alimuddin, Alimuddin; Arif, Moh. Syaiful (PROSIDING SEMINAR NASIONAL KIMIA; Vol 1 No 1 (2022): Prosiding SNK 2022, 2023)
Modification of Synthesis of Nanoparticles with L-Cysteine ​​functions as a capping agent/stabilizer, so that the nanoparticles can last longer. Modification of nanoparticle synthesis by adding L-Cysteine ​​to AgNPs and homogenizing it using a magnetic stirrer. Modification of nanoparticles (silverAgNPs) was monitored by observing the visible uptake. The results showed that the absorbance value increased by indicating the concentration of L-cysteine ​​5x10 -5 ; 6x10 -5 ; 7x10 -5 ; 8x10 -5 ; 9x10 -5 ; 1x10 -4 and the volume of L-cysteine ​​is 4 mL.